ANALYSIS OF GREEN ECONOMY AND BLUE ECONOMY IMPLEMENTATION TO IMPROVE SMEs AND SUSTAINABLE CREATIVE ECONOMY IN BERAU DISTRICT - Ratnasari, Warti (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to analyze the strategies for empowering MSME entrepreneurs and the Creative Economy, the concepts of blue economy and green economy that can influence MSME development and a Sustainable Creative Economy. This analysis uses independent variables, namely the empowerment of MSME entrepreneurs and the Creative Economy, the dependent variable is the increase in MSMEs and the Creative Economy and the moderating variables are the blue economy and green economy. The objects used in this study were MSME and Creative Economy entrepreneurs in Berau Regency with a sample of 170 people from Berau Regency from 13 sub-districts in Berau Regency and who had certain criteria. The data collection technique used in this study is probability sampling. The statistical method uses multiple linear regression analysis, with a statistical test to test the hypothesis t. This research was tested using Smart PLS and SPSS. This study uses a Likert scale with a 5-point scale to measure research variables. The results of this study indicate that the blue economy concept has a significant effect on increasing MSMEs and the Creative Economy, the green economy concept has a significant effect on increasing MSMEs and the Creative Economy, the strategies for empowering MSME entrepreneurs and the Creative Economy have no significant effect on increasing MSMEs and the Creative Economy in Berau Regency,